A morphosyntactic analysis of Arabic lexical borrowings in Badhini Kurdish / Karwan Waad Mosa - Karwan Waad, Mosa (2016)
This dissertation is an analytic study aims at investigating Arabic lexical borrowings in Badhini Kurdish dialect from morphosyntactic perspectives. It is confined to borrowings from Arabic in spoken Badhini Kurdish only. The fact that spoken Badhini Kurdish carries a heavy load of Arabic borrowings, which have greatly influenced its linguistic structure, and the lack of literature on this phenomenon motivated the researcher to categorize and describe the morphosyntactic processes in which Arabic borrowings found their way into Badhini Kurdish, and to find out the possible grammatical functions that they do in Badhini Kurdish. The data of this study has been culled from 50 TV interviews (40 hours in total) from 5 local Kurdish TVs namely; Badinan Sat, Spêde, Dohuk, Waar, and Delal, related to 12 different domains of knowledge. The obtained data was analyzed under the light of Haugen’s (1950) notions of borrowing; importation and substitution. The findings show that there is indeed a substantial number of words borrowed from Arabic through 16 different morphosyntactic processes that occur to their structures; 10 of which by pure morphemic importation called loanwords, 4 by morphemic importation and substitution or loan-blends, and 2 by morphemic substitution or loan-shifts. Among the outlined processes, Orthographically Assimilated Loanwords come at the highest percentage 44.01% followed by; Nuclear Loan-Blends 35.03%; Unassimilated Loanwords 13.82%; and Compound Loan-Blends 10.91%. Findings also demonstrate that Arabic lexical borrowings in this study can noticeably function as nouns (76.05%); followed by adjective (8.27%); adverbs (5.36%); as well as functional words (1.23%) and prepositions (0.61%). Besides, Arabic verbs are never seen directly borrowed from Arabic. However, Badhini Kurdish makes use of Arabic borrowings in forming verb loans, only, by combining Arabic nouns with native verb particles; more often with -ke ‘do’. Verbal usage of borrowings has the second largest percentage (8.45%) in this study. It is hoped that this study will positively contribute to the void of knowledge and raise our awareness and understanding of borrowing phenomenon in Badhini Kurdish. It will also be beneficial, especially, to students of linguistics and Kurdish speakers, in general, to understand better about the manner of Arabic lexical borrowings in Badhini Kurdish. Moreover, it might be insightful to policy makers and language reformers in standardizing Badhini Kurdish. Key Words: loanwords adaptation, lexical borrowings, morphosyntax, morphology, Badhini Kurdish, Arabic.